Różnica kwadratów wyrażeń algebraicznych
1.Uzupenij
a)
36x²-25y²= (....)² - (....)²= (....-....)(...+...)
b)
....-....=(....)²- (...)² = (3c-8d)(3c+8d)
c)
....-....=(2x)²-(3y)²=(...-...)(.....+...)
d)
(5a-4b)(5a+4b)=(...)²-(...)²=...-...

Prosze o szybkom pomoc :)
Zadanie na jutro :D

1

Odpowiedzi

2009-12-08T18:51:55+01:00
A)
36x²-25y²= (....)² - (....)²= (....-....)(...+...)

36x² - 25y² = (6x)² - (5y)² = (6x - 5y)(6x - 5y)


b)
....-....=(....)²- (...)² = (3c-8d)(3c+8d)
9c² - 64d² = (3c)² - (8d)² = (3c-8d)(3c+8d)


c)
....-....=(2x)²-(3y)²=(...-...)(.....+...)
4x² - 9y² = (2x)² - (3y)² = (2x - 3y)(2x + 3y)

d)
(5a-4b)(5a+4b)=(...)²-(...)²=...-...
(5a - 4b)(5a - 4b) = (5a)² - (4b)² = 25a² - 16a²

SzybkĄ :))

Pozdrawiam.